The Wiley Handbook on the Aging Mind and Brain 2018
DOI: 10.1002/9781118772034.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks, Social Relationships, and Their Effects on the Aging Mind and Brain

Abstract: Key Points• Increasing evidence shows the behavioral, perceptual, and biological pathways by which social relationships and social networks positively impact health outcomes, including those for the aging mind and brain The facilitation of healthy aging, in turn, has been shown to increase social participation among older adults through community-based interventions and contributes to societal well-being.• "Healthy Aging" as Physical, Mental, and Social Well-Being The World Health Organization (WHO) defines he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 148 publications
0
5
0
Order By: Relevance
“…Regarding marital status, the analysis did not find that this sociodemographic variable had any association, either on the ENCS or on the MMSE. In fact, the literature points to the importance of the quality of social relationships, stating that the existence of bonds does not guarantee the availability of supportive social resources [ 3 ]. This means that being married or having children does not necessarily mean that social relationships are satisfactory and of quality or that this network offers support for activities of daily living or for instrumental activities of daily living or promotes communication or mental functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding marital status, the analysis did not find that this sociodemographic variable had any association, either on the ENCS or on the MMSE. In fact, the literature points to the importance of the quality of social relationships, stating that the existence of bonds does not guarantee the availability of supportive social resources [ 3 ]. This means that being married or having children does not necessarily mean that social relationships are satisfactory and of quality or that this network offers support for activities of daily living or for instrumental activities of daily living or promotes communication or mental functions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the aging process is inevitable, epidemiological studies clearly show that diseases and functional disabilities, which are often associated with aging, are not inevitable [ 3 ]. However, it has been found that the increase in average life expectancy does not necessarily equate to an increase in years lived in good health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding marital status, no statistically significant differences were obtained. In fact, the literature points to the importance of the quality of social relationships, stating that the existence of bonds does not guarantee the availability of supportive social resources 3 . This means that being married or having children does not necessarily mean that social relationships are satisfactory and of quality or that this network offers support for activities of daily living or for instrumental activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of life cycle epidemiology (4)(5)(6), aging is largely determined by the lifestyles one adopts throughout life. In addition to individual factors, indirect factorssuch as organizational, community and political factors that support individual behavioralso contribute to these lifestyles (7), and the social environment has a predominant role (3). Thus, lifestyle is associated with the physiological changes that are characteristic of aging and often create conditions conducive to the development of multimorbidity.…”
Section: Introductionmentioning
confidence: 99%